Patterns of care contacts in the final year of life among opioid overdose fatalities in southern Sweden: a latent class analysis - Björn Johnson; Lisa Andersson; Helene Jacobsson; Ardavan M. Khoshnood (Harm Reduction Journal)
Abstract Background Understanding the heterogeneity of opioid overdose fatalities is critical to developing effective preventive interventions. This study examines patterns of care contacts among people who subsequently died from opioid overdose. The aim was to identify distinct groups of deceased individuals, based on their contacts with different care agencies in their last year of life. Methods A retrospective registry study was conducted in Skåne, Southern Sweden. All recorded opioid overdose fatalities during the study period were included, n = 191. Latent class analysis was used to identify patterns of care contacts in the last year of life. Results Three distinct classes were identified: “Few care contacts,” with limited interaction with any services; “Social service contacts,” comprising individuals who predominantly had contacts with the social services and, to a lesser extent, with prison and probation services; and “Numerous care contacts,” with extensive contacts with both healthcare and social services. The “few care contacts” class comprises about half of the population. This is an important finding, since this group has not been clearly visible in previous research. The analysis indicates significant gaps in service provision, particularly regarding substance use treatment and mental health support. Conclusions Using a person-centred approach, this article offers a novel way of analysing care contacts among people who subsequently died from opioid overdose. The identification of distinct groups, particularly a large group of people with minimal contact with the community care system, highlights the need for more targeted outreach and support work. Developing targeted interventions in emergency and inpatient care settings may provide an opportunity to reach the group with few care contacts.